“One Pill Makes You Larger and One Pill Makes You Small”: Queering Age and Time in Meow Wolf and “White Rabbit” - Sinwell, Sarah (Intermédialités / Intermediality, 2025)
This article explores the spaces of Meow Wolf’s “House of Eternal Return” in Santa Fe, New Mexico and the ways in which those spaces represent female adolescence and queer temporalities. Analyzing Evan + Zane’s music video for “White Rabbit” as a means of drawing on the interconnections between queer temporalities, growing up, and imagination, this article focuses on how queer time and queer kinship are represented in Lewis Carroll’s Alice’s Adventures in Wonderland, Meow Wolf, and “White Rabbit.”